Non-invasive stool antigen test for screening of Helicobacter pylori infection and assessing efficacy of treatment in patients with peptic ulcer (South East Asia Journal of Public Health, 2013)
Helicobacter pylori infection is one of the most common infections in humans, with an estimated 50% of the world population being infected.  The infection is strongly associated with chronic gastritis, peptic ulcer, adenocarcinoma and non-Hodgkins lymphoma of stomach. The prevalence of infection is high in developing countries, demanding a reliable diagnostic and treatment method. The present study was designed to investigate the monoclonal antibody-based H. Pylori stool antigen test to screen H. pylori infection and assess efficacy of treatment in patients with peptic ulcer. A total of 89 patients who underwent upper gastrointestinal endoscopy from July 2007 to June 2008 at Bangabandhu Sheikh Mujib Medical University Hospital, Dhaka, Bangladesh were included in the study. Endoscopic findings showed that out of 89 patients, 54 (60.7%) had duodenal ulcers, 24 (27%) had antral erosion and 5 (5.6%) had gastric ulcers. With RUT (rapid urease test) and histopathology of biopsy samples of 89 patients, 78 (87.6%) patients were found to be H. pylori positive. Stool antigen test was positive in 72 (92.3%) out of 78 H. pylori positive patients. The monoclonal stool antigen test (SAT) revealed 92.3% sensitivity and specificity of 100% before treatment. Among 52 follow-up patients (after treatment), 5 (9.6%) patients were detected positive by histology, RUT and stool antigen test, and 35 (67.3%) patients were negative by 3 tests. So the monoclonal SAT revealed 100% sensitivity and 100% specificity after treatment. The monoclonal stool antigen test is highly sensitive and a specific tool for diagnosis of H. pylori infection before therapy and can assess the success of eradication after therapy. It also offers the advantage of specificity and reliability over the invasive test.  It is easy and quick to use, non-invasive and does not require any special technology.South East Asia J Public Health | Jan-June 2012 | Vol 2 Issue 1 | 28-33 DOI: http://dx.doi.org/10.3329/seajph.v2i1.15262